2005
DOI: 10.1242/jeb.01570
|View full text |Cite
|
Sign up to set email alerts
|

Genomic sequences encoding two types of medaka hemopexin-like protein Wap65, and their gene expression profiles in embryos

Abstract: Medaka genomic BAC clones, which contained two types of medaka hemopexin-like protein gene (Wap65), mWap65-1 and mWap65-2, were screened and their genomic sequences were determined by the shotgun strategy. The exon-intron organizations were highly conserved between both mWap65s and human hemopexin genes. The 5′-flanking regions of mWap65-1 and mWap65-2 contained various putative transcription factor binding sites including elements for developmental regulation. The expression patterns of mWap65s during embryon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Further analyses on other fish species (Oncorhynchus mykiss, Ictalurus punctatus, Danio rerio, Oryzias latipes and Takifugu rubripes) have shown that in contrast to the single isoform found in mammals, wap65 is present in duplicate in fish, presumably as a result of the teleost whole genome duplication event (Amores et al, 1998). These fish isoforms display different affinities for haem, tissue distributions and development patterns (Hirayama et al, 2003;2004;Nakaniwa et al, 2005). In contrast to the eurythermal examples quoted earlier, some animals exist within a very narrow environmental temperature envelope.…”
Section: Introductionmentioning
confidence: 89%
“…Further analyses on other fish species (Oncorhynchus mykiss, Ictalurus punctatus, Danio rerio, Oryzias latipes and Takifugu rubripes) have shown that in contrast to the single isoform found in mammals, wap65 is present in duplicate in fish, presumably as a result of the teleost whole genome duplication event (Amores et al, 1998). These fish isoforms display different affinities for haem, tissue distributions and development patterns (Hirayama et al, 2003;2004;Nakaniwa et al, 2005). In contrast to the eurythermal examples quoted earlier, some animals exist within a very narrow environmental temperature envelope.…”
Section: Introductionmentioning
confidence: 89%
“…Wap65 was first detected as a glycoprotein in the plasma of goldfish (Kikuchi et al 1993) and has since been identified in medaka (Oryzias latipes), channel catfish (Ictalurus punctatus), swordtail fish (Xiphophorus hellerii), and fugu (Takifigu rubripes) (Kikuchi et al 1995;Kinoshita et al 2001;Hirayama et al 2003Hirayama et al , 2004Nakaniwa et al 2005;Aliza et al 2008). Teleost Wap65 shares significant sequence identity with mammalian hemopexin and has been suggested to play roles in iron homeostasis, antioxidant activity, bacteriostatic defense, nerve regeneration, transfer of heme, and the expression of genes known to promote cell survival (Delanghe and Langlois 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Warm-temperature-acclimation-related 65-kDa protein contains hemopexin-like repeats which occur in vitronectin and some matrix metalloproteinase families such as collagenases, stromelysins, and other enzymes that metabolize the extracellular matrix. It may be important in the remodeling of the extracellular matrix and play an important role during early development (Nakaniwa et al 2005). It was upregulated at D13 and D23 but had decreased by D33.…”
Section: Discussionmentioning
confidence: 99%